Pengaruh Metode Bercerita Dengan Buku Cerita Bergambar Terhadap Konsentrasi Belajar Anak Kelompok B Di Tk Pertiwi Jaten 2 JuwiringKlaten Tahun Ajaran 2016/2017 - Murniati, Nika, Sri Slamet,S.Pd., M.Hum., M.Pd (2017)
This research aimed to know the influence of telling story method using pictured story books toword the leraning concentration of group B students at TK Pertiwi Jaten 2 Juwiring Klaten in the academic year of 2016/2017. The method implemented in this research was quantitative method using pre-experimental design. This research was conducted to 12 students at TK Pertiwi Jaten 2 Juwiring Klaten. The data were gained by observation, interview, documentation, and tests (pretest-posttest). The data analysis technique in this research used SPSS 16.0 for Windows. The result of the data analysis using t-test showed that t-calc -8.680 ≤ t-table -1.7959, meaning that Ho was rejected and Ha was acceped. Therefore, it can be concluded that there is the impact of telling story technique using pictured story books toword the dtudents learning concentration. Key words: Telling story method, pictured story books, learning concentration